Kinetics of interface alloy phase formation at nanometer length scale in ultra-thin films: X-ray and polarized neutron reflectometry. (July 2018) - Singh, Surendra; Swain, Mitali; Basu, Saibal
Abstract: Multilayer thin films of various metal pairs present model systems for studying intermetallic alloy phase formation at interfaces of these heterostructures on annealing and help to understand the kinetics of phase formation. Formation and study of these phases at the interfaces is of deep interest with respect to application and for understanding microscopic kinetics in ultra-thin layers. Also intermetallic phases are known to have extraordinary functions and characteristics that are not observed in bulk metals and alloys. Many intermetallic alloys exhibit attractive combination of physical and mechanical properties, such as high melting point, low density, high strength, good oxidation and creep resistance. In the past two decades X-ray and neutron reflectometry have been established as important non-destructive tools for obtaining physical and magnetic properties in thin film multilayers with sub-nanometer spatial resolution. All the major neutron and synchrotron sources at present provide variants of these techniques, dedicated to studies related to layered structures. This article reviews very slow diffusion at the interfaces of heterostructures, discerning kinetics of intermetallic phase formation at the interfaces in thin films and multilayers on annealing at relatively lower temperatures, primarily using X-ray and neutron reflectivity techniques. It highlights the strength of X-ray reflectivity (XRR) and neutron reflectivity (NR) to measure very low diffusivity (typically ∼10 −19 –10 −23  cm 2 /s) in thin films. We will specifically discuss interdiffusion and formation of binary intermetallic alloys on annealing of several Ni based multilayers, with special emphasis on Ni/Ti, Ni/Al and Ni/Ge multilayers to demonstrate the strength of these techniques. These are well known systems for technological application in the field of shape memory alloys, in aeronautical industries and as corrosion resistant low-resistance contact on semiconductor surface. Especially Ni/Al has been studied at length by many workers in the past for its technological importance. It is a model system for extending several concepts in phase formation kinetics from bulk to thin films. Important studies include effect of interface morphology on phase formation, identification of a kinetic length scale of diffusion and estimation of exact composition of alloy phase at interfaces on annealing the multilayers and self-diffusion in isotopic multilayers. These parameters are responsible in controlling various material composition and properties. We have devised a formalism that uses measurements of XRR and NR on a sample to identify the composition of the binary alloy phase at the interface. This proves to be extremely helpful to estimate composition of an ultra-thin alloy layer of few nanometer thicknesses. Often these alloy phases are either non-stoichiometric or too thin for detection by X-ray diffraction technique. The present review article also includes the effect of interdiffusion on interface magnetism of magnetic/non magnetic multilayers of technological interest, using polarized neutron reflectometry.